Efficacy of C&D waste in base/subbase layers of pavement – current trends and future prospectives: A systematic review. (18th July 2022) - Mohanty, Monika; Mohapatra, Smruti Sourava; Nayak, Sanket
Highlights: Systematic review has been performed on Scopus and Web of Science (WoS) databses, and 122 studies were appraised. Various C&D waste materials have been reviewed to find their potential usage as subbase/base material in the pavement. Influence of C&D waste as an alternative aggregate was assessed in terms of mechanical and durability properties. Opportunities and drawbacks associated with the application of C&D waste in the subbase/base of pavement are discussed. Research gaps in existing literature are critically identified and future prospectives are judiciously proposed. Abstract: Construction and demolition (C&D) waste consists of debris generated from construction, repair, renovation, and demolition of bridges, roads, buildings, and other infrastructure. It has certain adverse environmental impacts resulting in the consumption of valuable land space, landfill depletion, consumption of energy, and non-energy resources, resource depletion, pollution, etc. This paper presents a systematic review of literature on research pertaining to the usage of different types of C&D wastes as aggregate in the bound and unbound subbase or base layers of pavement. The literature search on two databases, namely: Web of Science (WoS) and Scopus, resulted in 7610 records. After adopting inclusion and exclusion criteria, the full text of 122 records is critically assessed. The efficacy of utilization of C&D waste in base or subbase layers in terms of mechanical and durability properties has been critically reviewed. California bearing ratio (CBR), and unconfined compressive strength (UCS) value of blended C&D waste materials are found to decrease with an increase in waste content in the mix. However, chemical stabilization could result in the enhancement of both properties. The resilient moduli for these waste materials are found to be enhanced with an increase in stabilizer dosage, curing duration, and confining pressure. Similarly, the permanent deformation of treated C&D waste materials has shown a decreasing trend with an increase in the stabilizer content. The addition of recycled asphalt pavement (RAP) aggregates to the cement-treated base reduced the flexural strength but enhanced the ductile behaviour. Research gaps are identified critically and future prospectives are proposed. Evaluation of the suitability of unexplored wastes for subbase or base layers applications is suggested. The comprehensive information enlisted in this paper may serve as a guideline for adopting non-traditional aggregates in base or subbase layer construction. Further, the outcome of this investigation is expected to be beneficial to adjudge suitable construction practices to accelerate waste utilization for sustainable pavement construction.